TINGKAT DISTORSI HARMONISA PADA LAMPU ESSENSIAL YANG BERBEDA MERK - Luqman Assaffat (MEDIA ELEKTRIKA, 2012)
Essential Lamp (SL) is a type of low pressure mercury lamp that works on the discharge ofelectrons inside the tube and using an electronic switch equipment as a replacement ballast forlimiting the current function. Because of the working principle, the essensial lamp can beclassified as a non-linier electrical loadIn the electric power system, a non linear loads will produce an electrical power pollution.It is called harmonics. Harmonics are multiples of the frequency of a fundamental frequency ofwave. Harmonics generated by the non-linier loads that will accumulate and delivered to thepower system. So the harmonics will be able to disrupt the power quality of electrical powersystems.As a non-linear load, essential lamps produce harmonic distortion, both harmoniccurrents and voltage. In this study concluded that the different brands of essential lamp showed thedifferent value of Total HarmonicsDistortion (THD)